Penggunaan Aplikasi Wattpad Sebagai Media Dakwah (Studi Pada Penulis Novel Indahnursf) - Sari , Rica Ayu Permata; Hasmawati , Fifi; Manalullaili , Manalullaili (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This research is entitled "Use of the Wattpad Application as a Da'wah Media (Study of the Novel Writer Indahnursf)". The problem formulation in the research is how to apply Wattpad as a medium for writing novels that contain elements of da'wah messages for the writer Indahnursf. The purpose of this research is to find out that the Wattpad application for writing novels by Indahnursf can be used as a medium for conveying da'wah messages. This research uses a qualitative research method with a content analysis approach. The data collected is in the form of documentation and interviews. And the data analysis technique uses content analysis techniques. The results of the research explain that Indahnursf's use of the Wattpad application for writing novels can be an effective medium for conveying da'wah messages. This can be seen from the results of Indahnursf's novels entitled The Most Beautiful Hijrah, Jodoh, Qalbu, and At the End of the Prayer of Love, which contain preaching messages. The categories of da'wah messages contained in the novel Indahnursf are, Novel Jodoh contains a message of faith, namely faith in Allah, a moral message, namely sincerity. And also sharia, namely worship. The Most Beautiful Hijrah Novel contains a sharia message, namely worship, a moral message, namely gratitude, and a creed message, namely Faith in Allah. Then, the novel Di Penghujung Doa Cinta contains a sharia message, namely worship and muamalah, a moral message, namely gratitude, helping each other and reminding each other of goodness, and a creed message, namely faith in Allah and faith in Qodo and Qodar. Lastly, Novel Qalbu contains a sharia message, namely the prohibition of approaching adultery, a creed message, namely faith in Allah, and a moral message, namely patience and gratitude.